Inappropriate use of propranolol among medical students in Palestine: cross-sectional study - Omar Younis; Mohammad Taleb Abed; Yaqoot Anabseh; Suha Hamshari; Mahfouz Ktaifan; Sa’ed H. Zyoud (BMC Medical Education)
Abstract Introduction Medical students’ inappropriate propranolol use, driven by exam stress, is a developing concern. This study examined propranolol misuse among Palestinian medical students at An-Najah National University. Methodology This is a cross-sectional study that included second to sixth-year medical students at An-Najah National University in Palestine. An online self-administrated Arabic questionnaire was developed by researchers. This 29-question, three-section questionnaire was sent to eligible participants via university email and student Facebook groups. The data collection period extended from August to September 2023. Results A total of 401 students participated in the survey. The majority of the respondents were females (227, 57%) and final-year medical students (137, 34%). The utilization of propranolol was identified in 12% in our study. About 60% engaged in self-prescribing doses ranging between 10 and 20 mg, with 56% falling within this range. The main motivation for self-prescribing was to alleviate anxiety symptoms (88%), particularly before objective structured clinical examinations (OSCEs) (89%) or presentations (39%). 68% of students expressed awareness of the potential side effects. Statistical analysis revealed significant associations between propranolol use and factors such as age (p < 0.001), academic year (p < 0.001), the presence of chronic diseases (p = 0.011), and psychoactive drug use (p = 0.045). Conclusion Propranolol was used by 12% of the surveyed medical students, with 89% of its users taking it before OSCEs. Despite being aware of its potential side effects, many students still chose to self-medicate, highlighting the role of stress-induced behavior. This emphasizes the importance of stress management strategies before difficult occasions in medical students’ journey.